Analisis Luas Daerah Rawan Banjir Kota Medan Berbasis Sistem Informasi Geografis (SIG) - Indri Triawati; Annisa Nur Rakhmawati; Wahyu Nursamhuda (Journal of Innovative and Creativity, 2025)
Medan City is an urban area that frequently experiences flooding during the rainy season. This study aims to analyze the extent of flood-prone areas in Medan City using Geographic Information System (GIS) technology. The research method was carried out through a georeferencing process on flood-prone area maps and the creation of shape files to calculate the area affected by flooding. The data used included flood vulnerability parameters and water inundation maps, which were then processed using QGIS software. The analysis results show that areas with a low level of flood vulnerability cover an area of ​​approximately 2,844 hectares (10.72%), areas with a moderate level of vulnerability cover 8,642.4 hectares (32.6%), and areas with a high level of vulnerability cover 14,632 hectares (55.2%). These findings indicate that more than half of Medan City's area is categorized as moderate to severe flood prone. Therefore, more effective mitigation measures and spatial planning management are needed to minimize the risk of future flood disasters.